Descripción de un caso de violencia de género en una comunidad Kichwa de Cotacachi - Cevallos, Concepción E. (2021)
This research work describes a case of gender violence through the Application of Indigenous Justice in a Kichwa community in the Cotacachi canton (Ecuador), for which several contributions from jurists and community leaders have been taken into consideration who worked on the issue of the administration of Indigenous Justice from the principles, values, beliefs, uses, customs and community traditions counteracted to the application of the legal norms for the protection of human rights. Under this context, We will reflect on the role of Legal and Forensic Psychology, since in Ecuador, the Violence against indigenous women is a common practice and they tend to face different forms and successive episodes of historical discrimination in their communities (Jerez, 2019).